Trade liberalization under CAFTA: an analysis of the agreement with special reference to agriculture and smallholders in Central America - Morley, Samuel (International Food Policy Research Institute, 2006)
This paper is a description and an analysis of trade liberalization under CAFTA. It shows that in the short run the impact of the agreement is likely to be small... Since the U.S. already grants tariff-free access under the CBI, trade liberalization in the CAFTA treaty appears to be asymmetric, with most of the tariff reductions being granted by the Central American countries. That is misleading for two reasons. First there really were some significant tariff barriers in the United States for agricultural commodities under the CBI. Many of these are removed under CAFTA. Second, the current favorable special treatment of the five Central American countries under the CBTPA and the CBI will expire in 2008 if CAFTA is not implemented. CAFTA makes permanent the tariff concessions of the CBI and the liberalized rules of origin of the CBTPA... The fact that the tariff reductions and TRQs granted by the Central American countries under CAFTA will not cause significant price reductions does not mean that domestic producers will be unaffected by the agreement. In the long run the level of protection of many important commodities such as rice, pork and poultry will be significantly lower. But the tariff reductions in these sectors are gradual. That gives farmers time to adjust and to become more competitive. What will be critical from a policy perspective is that this time is used wisely to increase productivity, switch to more profitable crops and take advantage of the new opportunities opened up by CAFTA..